Bioefficacy of different botanical oils against maize weevil, Sitophilus zeamais (M.) at medium altitude hills of Meghalaya (Indian Journal of Hill Farming, 2024)
The bioefficacy of various botanical oils were evaluated for the management of maize weevil, Sitophilus zeamais (M.) at the laboratory conditions of ICAR-RC for North Eastern Hill Region, Barapani, Meghalaya. Different vegetable oils viz., coconut, castor, mustard, soybean, sunflower and neem oil were tested for mortality, adult emergence and loss in terms of grain damage and loss in weight of kernels. Amongst them, neem oil was the most effective at both the doses (1ml and 3ml/kg grain). Cent per cent mortality was obtained in grains treated with oils of neem and mustard @ 3ml/kg grains. There was no weight loss and grain damage in treatment with neem oil @ 3ml/kg grain and adult emergence was found to be completely inhibited. Lowest weight loss was obtained in mustard oil treated maize grains followed by maize grains treated with soybean oil (0.75 %). Highest weight loss (2.27 %) was obtained in coconut oil treated maize grains. Highest grain damage (6.38 %) was obtained in maize grains treated with soybean oil and lowest damage (1.79 %) was observed in mustard oil treated grains. The treatment with oils had no negative impact on the germination of the grains.